C. Bledsoe, S. Lerner y J. Guyer (eds.) Fertility and the male life cycle in the era of fertility decline. Oxford : Oxford University Press : IUSSP International Studies in demography, 2000 - Szreter, Simon (Estudios Demográficos y Urbanos, 2001)
C. Bledsoe, S. Lerner y J. Guyer (eds.). Fertility and the Male Life Cycle in the Era of Fertility Decline, Oxford, Oxford University Press/lUSSP International Studies in Demography, 2000.